The Incorporation Of Green Spaces Into Urban Settings: Approaches For The Creation Of Sustainable Urban Landscapes - Wei, Yang; Muralitharan Doraisamy Pilla, Muralitharan Doraisamy Pilla (Journal of Neonatal Surgery, 2025)
This paper aims to analyse the advantages and disadvantages of urban green zones by means of analysis and synthesis of research results from many areas. One cannot stress the value of green areas for the growth of sustainable development. Included in the mix are social, cultural, environmental, and financial elements. Parks and other green areas—even metropolitan ones—may one day show to be a useful weapon in the battle against environmental deterioration. This is justified by their various positive effects on air quality, property value (because of their appeal and the facilities they provide), and energy consumption (because of lower building cooling demand). Both locals and visitors find great attraction in recreational and leisure facilities as they are among the ecological benefits that urban green areas might provide. Justifying the many purposes of green spaces means include into environmental sustainability agendas the suitable distribution of green areas within urban areas and qualitative development. If cities all across the world are committed to reach environmental sustainability, they have to create a coordinated strategy for the creation, maintenance, and improvement of green areas in urban settings. The idea of sustainable development has become more important for handling a variety of social, economic, and environmental problems; the alarming reduction of green spaces in contemporary, highly crowded cities raises serious questions about the long-term survival of these places. Reflecting the diverse aspect of urban green space, this work uses and evaluates materials anchored in transdisciplinary and multidisciplinary approaches. Urban green ideas for revitalisation and expansion should mostly emphasise integrating more green spaces into built environments